Searching for Effective Treatments in HFpEF: Implications for Modeling the Disease in Rodents - Magdalena Jasińska-Stroschein (MDPI AG, 2023)
Background: While the prevalence of heart failure with preserved ejection fraction (HFpEF) has increased over the last two decades, there still remains a lack of effective treatment. A key therapeutic challenge is posed by the absence of animal models that accurately replicate the complexities of HFpEF. The present review summarizes the effects of a wide spectrum of therapeutic agents on HF. Methods: Two online databases were searched for studies; in total, 194 experimental protocols were analyzed following the PRISMA protocol. Results: A diverse range of models has been proposed for studying therapeutic interventions for HFpEF, with most being based on pressure overload and systemic hypertension. They have been used to evaluate more than 150 different substances including ARNIs, ARBs, HMGR inhibitors, SGLT-2 inhibitors and incretins. Existing preclinical studies have primarily focused on LV diastolic performance, and this has been significantly improved by a wide spectrum of candidate therapeutic agents. Few experiments have investigated the normalization of pulmonary congestion, exercise capacity, animal mortality, or certain molecular hallmarks of heart disease. Conclusions: The development of comprehensive preclinical HFpEF models, with multi-organ system phenotyping and physiologic stress-based functional testing, is needed for more successful translation of preclinical research to clinical trials.